A novel asexual blood-stage malaria vaccine candidate: PfRipr5 formulated with human-use adjuvants induces potent growth inhibitory antibodies - Takashima, Eizo; Nagaoka, Hikaru; Correia, Ricardo; Alves, Paula M.; Roldão, António; Christensen, Dennis; Guderian, Jeffrey A.; Fukushima, Akihisa; Viebig, Nicola K.; Depraetere, Hilde; Tsuboi, Takafumi (Frontiers in Immunology, 2022)
PfRipr is a highly conserved asexual-blood stage malaria vaccine candidate against Plasmodium falciparum. PfRipr5, a protein fragment of PfRipr inducing the most potent inhibitory antibodies, is a promising candidate for the development of next-generation malaria vaccines, requiring validation of its potential when formulated with adjuvants already approved for human use. In this study, PfRipr5 antigen was efficiently produced in a tank bioreactor using insect High Five cells and the baculovirus expression vector system; purified PfRipr5 was thermally stable in its monomeric form, had high purity and binding capacity to functional monoclonal anti-PfRipr antibody. The formulation of purified PfRipr5 with Alhydrogel®, GLA-SE or CAF®01 adjuvants accepted for human use showed acceptable compatibility. Rabbits immunized with these formulations induced comparable levels of anti-PfRipr5 antibodies, and significantly higher than the control group immunized with PfRipr5 alone. To investigate the efficacy of the antibodies, we used an in vitro parasite growth inhibition assay (GIA). The highest average GIA activity amongst all groups was attained with antibodies induced by immunization with PfRipr5 formulated with CAF®01. Overall, this study validates the potential of adjuvanted PfRipr5 as an asexual blood-stage malaria vaccine candidate, with PfRipr5/CAF®01 being a promising formulation for subsequent pre-clinical and clinical development.